Effect of diffuse panbronchiolitis critical region 1 polymorphisms on the risk of aspirin-exacerbated respiratory disease in Korean asthmatics - Lee, Jin Sol; Bae, Joon Seol; Kim, Jeong-Hyun; Kim, Jason Yongha; Park, Tae Joon; Pasaje, Charisse Flerida A; Park, Byung-Lae; Cheong, Hyun Sub; Uh, Soo-Taek; Park, Jong-Sook; Park, Choon-Sik; Shin, Hyoung Doo (Respiratory care, 2012)
The functional role of the human diffuse panbronchiolitis critical region 1 (DPCR1) gene, located in the major histocompatibility complex class I, has not been widely investigated. However, this gene is a well known genetic marker for diffuse panbronchiolitis, a disease affecting human respiratory bronchioles. In this study we explored the association between polymorphisms in DPCR1 and aspirin-exacerbated respiratory disease (AERD), an asthma phenotype. Genotyping of 6 polymorphisms was carried out in a total of 189 Korean asthmatic patients stratified into 93 AERD cases and 96 aspirin tolerant asthma controls. Subjects who exhibited significant decrease of FEV(1) by aspirin provocation were identified as AERD subjects. Logistic and regression analyses were performed to investigate the association between DPCR1 polymorphisms and the risk of AERD as well as FEV(1) decline. Initial analysis revealed significant association of rs2517449 with AERD, with a P value of .03 via a recessive model; however, the association signal disappeared after multiple testing corrections. In addition, rs2517449 and rs2240804 also showed association signals with decline of FEV(1) after aspirin provocation (P = .007 and .03, respectively, in a recessive model). After testing for multiple comparisons, only the association signal from rs2517449 was retained (P(corr) = .04), while other polymorphisms showed no associations with the risk of AERD and FEV(1) decline. Our results show that polymorphisms in DPCR1 are not associated with the risk of AERD.